Pengaruh Motivasi Belajar dan Kedisiplinan Terhadap Prestasi Belajar Siswa Pada Muatan IPA di SD Negeri 1 Tigawasa - Indah Novitayani, Ni Putu; Redan Werang, Basilius; Rati, Ni Wayan (Universitas Hamzanwadi, 2025)
This research aims to find out how learning motivation and discipline influence student learning achievement in science learning content at SD Negeri 1 Tigawasa. The type of research used in this research is quantitative research with a descriptive approach. The design used in this research is a survey research design. The population of this research is all students at SD Negeri 1 Tigawasa, totaling 156 students. The sampling method used in this research was purposive sampling. The subjects of this research were students in grades IV, V and VI at SD Negeri 1 Tigawasa, totaling 76 students. This research was conducted by distributing linker-sized questionnaires. This research uses causal quantitative data, namely data that can be calculated or data in the form of numbers. The analysis technique in this research is multiple linear regression analysis with data processing using SPSS. The results of the coefficient of determination test with an R2 value of 0.705, this proves that learning motivation and discipline influence student learning achievement by 70.5% and 29.5% are influenced by other variables. Based on the t-test, the results of the first hypothesis have a probability value of 0.000 < 0.05, proving that learning motivation has a positive and significant effect on learning achievement, while the second hypothesis has a probability value of 0.004 < 0.05 so that discipline has a positive and significant effect on learning achievement, and for The third hypothesis has a probability value of 0.000 > 0.05, this proves that learning motivation and discipline have a positive and significant effect on learning achievement. Future researchers are advised to develop the research model by adding intervening or moderating variables to create a more complex research model and provide more comprehensive results.